Occipitoatlantal Dislocation - Garrett, Mark; Consiglieri, Giacomo; Kakarla, Udaya K.; Chang, Steve W.; Dickman, Curtis A. (Neurosurgery, 2010)
Abstract OCCIPITOATLANTAL DISLOCATION (OAD) can be devastating. This injury may be fatal in many cases, but more survivors are reported because of improvements in diagnosis and treatment. This article describes the diagnosis and treatment of OAD. To diagnose and treat OAD appropriately, neurosurgeons must have a detailed understanding of the anatomy of the craniocervical junction. Various radiographic criteria are used to establish the diagnosis of OAD. A destabilizing injury such as OAD requires surgical fixation. Many surgical techniques are available for fixation of the craniocervical junction. Future studies will continue to refine the diagnostic criteria for OAD and to develop improved methods for craniocervical stabilization.